Tourists’ Destination Loyalty is leading for Perceived Sustainable Tourism (Reference to Tourists’ Cultural Destinations in Sri Lanka) - Udurawana, Y.M.W.G.P.K.; Wanninayake, W.M.C.B.; Laksiri, W.M.R.; Pratheepkanth, P. (University of Kelaniya, 2021)
As the leading industry, tourism has developed many cultural destinations sustainably through loyal tourists. Therefore, Sri Lanka has included many tourists loyalty program to keep tourists, while promoting the eight world heritage sites with the 2000 year aged history. However, except Sigiriya and Polonnaruwa, all other cultural places have attracted a few tourists within the recent five years. Meanwhile, there were very limited researches to discuss the effect of loyalty to sustainability. The main objective of the study was to identify the effect of destination’s loyalty on sustainable tourism. 513 tourists represented the sample from the tourists who visited Sri Lanka in the year 2019. Data collected through well-developed questionnaire, the results proved that loyalty is leading for sustainable tourism. Finally, researchers purposed strategies to relevant authorities to develop many exciting activities with greater hospitality attached to cultural areas to enhance tourists’ loyalty for sustainable tourism.
Keywords: Tourists’ Destination Loyalty; Sustainable Tourism; Sustainable Tourism